Biological Population of Torpedo Scad (Megalaspis cordyla) in The Waters of Lampung Bay - Kartini, Nidya; Caesario, Rachmad; Utomo, Deny Sapto Chondro; Delis, Putu Cinthia (Jurnal Biologi Tropis, 2025)
Megalaspis cordyla, a demersal fish popularly referred to as torpedo scad, is the most commonly caught fish. As market demand and consumption rise, this will have an adverse effect on the sustainability of fish resources if improperly managed. The aim of this research was to analyze the population dynamics of Megalaspis cordyla in the waters of Lampung Bay. The study was carried out between April and September of 2024. Fishermen's catches in the waters surrounding Lampung Bay provided the Bekre fish used in the study. The study's findings demonstrated that bekre fish have a negative allometric growth trend. The value of the condition factor falls between 0.631 and 0.966. Fishing mortality (F) is 3.46 per year, total mortality (Z) is 4.59 per year, and exploitation rate (E) is 0.75 per year. The natural mortality value (M) of bekre fish is 1.13 per year, as are the values of the growth parameters of bekre fish, specifically Linf of 456 mm, growth coefficient (K) of 1.51 per year, and t0 of -0.049. March and October saw the highest bekre fish recruitment rates in Lampung Bay's waters, with 32.55% and 9.04%, respectively.